(untitled) (Annals of Medical Research, 2023)
Aim: The aim of this retrospective study is to examine the frequency and clinical features of skin lesions in patients with sarcoidosis and to compare them with the literature. Materials and Methods: The files of patients diagnosed with sarcoidosis in the last 10 years in our hospital were reviewed retrospectively. Age, gender, age at diagnosis, dermatology consultation or dermatological examination findings were recorded for all patients. Results: Thirty (69.8%) of the patients diagnosed with sarcoidosis were female and 13 (30.2%) were male. The mean age was 49.7 ± 12.2. When the patients are grouped according to the age ranges at which they are diagnosed, there are 1 (%2.3) patient between the ages of 10-19, 4 (%9.3) patients between the ages of 20-29, 6 (%13.9) patients between the ages of 30-39, 16 (%37.2) patients between the ages of 40-49, 8 (%18.6) patients between the ages of 50-59 and 8 (%18.6) patients over the age of 60. The mean age at which female patients were diagnosed with sarcoidosis was 47.56±12.85, and the mean age at which male patients were diagnosed with sarcoidosis was 41.86±13.81 years. The mean follow-up period of the patients was 4.0±3.1 years. Thirty-one (72.1%) of all patients were examined in dermatology. Dermatological findings including erythema nodosum were detected in 8 (18.6%) patients. Conclusion: Sarcoidosis is a multisystemic disease that can progress with various clinical findings and should be considered in the differential diagnosis with its frequent or rare findings. In this study, in which the data of patients diagnosed with sarcoidosis in the last 10 years in our hospital were evaluated, our findings were generally similar to the literature data.